Neural Damage in Experimental Trypanosoma brucei gambiense Infection: Hypothalamic Peptidergic Sleep and Wake-Regulatory Neurons - Laperchia, Claudia; Xu, Yuan-Zhong; Mumba Ngoyi, Dieudonné; Cotrufo, Tiziana; Bentivoglio, Marina (Frontiers in Neuroanatomy, 2018)
Neuron populations of the lateral hypothalamus which synthesize the orexin (OX)/hypocretin or melanin-concentrating hormone (MCH) peptides play crucial, reciprocal roles in regulating wake stability and sleep. The disease human African trypanosomiasis (HAT), also called sleeping sickness, caused by extracellular Trypanosoma brucei (T. b.) parasites, leads to characteristic sleep-wake cycle disruption and narcoleptic-like alterations of the sleep structure. Previous studies have revealed damage of OX and MCH neurons during systemic infection of laboratory rodents with the non-human pathogenic T. b. brucei subspecies. No information is available, however, on these peptidergic neurons after systemic infection with T. b. gambiense, the etiological agent of 97% of HAT cases. The present study was aimed at the investigation of immunohistochemically characterized OX and MCH neurons after T. b. gambiense or T. b. brucei infection of a susceptible rodent, the multimammate mouse, Mastomysnatalensis. Cell counts and evaluation of OX fiber density were performed at 4 and 8 weeks post-infection, when parasites had entered the brain parenchyma from the periphery. A significant decrease of OX neurons (about 44% reduction) and MCH neurons (about 54% reduction) was found in the lateral hypothalamus and perifornical area at 8 weeks in T. b. gambiense-infected M. natalensis. A moderate decrease (21% and 24% reduction, respectively), which did not reach statistical significance, was found after T. b. brucei infection. In two key targets of diencephalic orexinergic innervation, the peri-suprachiasmatic nucleus (SCN) region and the thalamic paraventricular nucleus (PVT), densitometric analyses showed a significant progressive decrease in the density of orexinergic fibers in both infection paradigms, and especially during T. b. gambiense infection. Altogether the findings provide novel information showing that OX and MCH neurons are highly vulnerable to chronic neuroinflammatory signaling caused by the infection of human-pathogenic African trypanosomes.